Malnutrition-Sarcopenia Syndrome: Is This the Future of Nutrition Screening and Assessment for Older Adults? - Maurits F. J. Vandewoude; Carolyn J. Alish; Abby C. Sauer; Refaat A. Hegazi (Journal of Aging Research)
Malnutrition is common across varying patient populations, particularly older adults, and sarcopenia prevalence increases with advancing age. Both malnutrition and sarcopenia are associated with substantial adverse outcomes affecting both the patient and the healthcare system, including increased morbidity, mortality, rehospitalization rates, and healthcare costs. Healthcare practitioners may assess patients for either malnutrition or sarcopenia; however, many patients clinically present with both conditions, resulting in the syndrome, Malnutrition-Sarcopenia Syndrome, which is the clinical presentation of both malnutrition and accelerated age-associated loss of lean body mass, strength, and/or functionality. Clinicians are urged to screen, assess, and treat these conditions currently so as to adequately address the full spectrum of patients’ nutritional issues. By examining aspects of both conditions, clinicians can more fully assess their patients’ clinical and nutritional status and can tailor targeted therapies to meet their needs and improve outcomes. This proposed syndrome embodies the inherent association of malnutrition and sarcopenia, highlighting their combined impact on clinical outcomes. The objective of this review paper is to characterize Malnutrition-Sarcopenia Syndrome to advance clinical practice, by providing clinicians with the necessary background information to integrate nutritional assessment along with loss of muscle mass and functionality in their everyday clinical practice.